RESEARCH OF USING OF ADDITIONAL COPPER PLATING OF BRASS COVERING IN THE LINE OF STEEL WIRE BRASS PLATING - Yu. L. Bobarikin; M. N. Vereschagin; S. I. Prach; E. V. Shamanovskaja; A. V. Vengura; A. V. Vedeneyev; O. Yu. Vinokurova (Литьë и металлургия, 2012)
The results of investigations showed that using of additional application of copper by means of wire cooling after diffused application of brass covering yielded positive results.